Adaptive Reasoning, Mathematical Problem Solving and Cognitive Styles - Yanti, Aning Wida; Budayasa, I Ketut; Sulaiman, Raden (JTAM (Jurnal Teori dan Aplikasi Matematika), 2021)
The purpose of this research finds a link between adaptive reasoning, mathematical problem solving, and cognitive style. This research is a literature study. This paper showed the relationship between adaptive reasoning, mathematical problem solving, and cognitive styles. In particular, field-independent (FI) and field-dependent (FD) cognitive styles. Adaptive reasoning in mathematical problems is the legitimacy of problem strategies. Whereas the cognitive style provides opportunities for students to give reasonable arguments according to the tendency of the cognitive style. Mathematical problem-solving in the FI and the FD can vary according to students' cognitive styles. It was found that adaptive reasoning, mathematical problems, cognitive styles (FI, FD) have a strong stylistic relationship where adaptive reasoning will be able to give direction to students in solving math problems. Therefore, the basis for researching the adaptive reasoning profile of students in solving mathematical problems in terms of FI and FD cognitive styles is our understanding of the relationship between adaptive reasoning, mathematical problem solving, and cognitive style